Kewirausahaan produk olahan susu dan durian untuk pengembangan ekonomi kreatif desa Wonomerto Jombang - Siti Muhimatul Khoiroh; Mohammad Insan Romadhan; Herlina Herlina (Penerbit Goodwood, 2021)
Purpose: Wonomerto Village is a durian and milk-producing village; besides, the majority of the people work as rice farmers. Durian and milk are a side business that is used as additional income during the waiting period for harvest. The price is quite low than the price of durian or milk in cities. This is a problem for the government who wants to raise the village's natural products as a potential business to support the tourism program of the City of Jombang. Method: A 4-stage work program was compiled to solve the problems of Wonomerto Village partners, namely socialization, implementation, evaluation and reporting. The implementation of partnerships in the field of entrepreneurship in the form of processing milk production, durian, as well as online packaging and marketing techniques by utilizing a mini studio made from affordable materials to penetrate the online market. Results: The results of this training program are that the community is able to make various processed products with added value, such as milk candy, fresh milk variants, durian pies, and durian milk cakes with attractive packaging to be marketed in various tourist attractions in Jombang. Conclusions: This training has a positive impact in increasing understanding of innovation and technology by 70% as well as interest in innovation for increasing the existence of the creative industry in Wonomerto Village. Keywords: Product innovation, Milk, Durian, Packaging, marketing